Digital Culture and Youth Development: Assessing the Influence of TikTok on Adolescents in Makassar. - Genisa, Risma Asriani Azis; Masdianti, Masdianti; Suhartini, Titin; Syamsuddin, Syamsuddin; Gau, Muhammad Resky A. (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2026)
The growing presence of digital media has transformed how adolescents interact, construct values, and engage with their social environment. TikTok, as one of the most popular platforms among Indonesian youth, plays a central role in shaping contemporary digital culture. This study examines how TikTok influences adolescents’ social interactions, moral values, and awareness of social issues in Maccini Parang, Makassar. Using a quantitative descriptive approach, data were collected through a structured questionnaire distributed to adolescent respondents who actively use TikTok. The instrument measured perceptions related to patterns of social interaction, moral considerations, and behavioral responses to content encountered on the platform. Descriptive statistical analysis was employed to identify dominant tendencies and variations in responses. The findings indicate that most adolescents engage intensively with TikTok and are frequently exposed to content they perceive as distracting or inappropriate, such as non-educational material, sensational trends, and morally questionable behavior. Despite this exposure, the results also show that many adolescents demonstrate a degree of critical awareness and self-regulation by selectively filtering content they consider negative or irrelevant. While some respondents acknowledged that TikTok influences their real-life decisions and moral perspectives, others maintained that their values remain largely shaped by family, school, and community norms. These findings suggest that TikTok’s influence on youth development is neither uniform nor deterministic but mediated by adolescents’ agency and local socio-cultural contexts. This study contributes to discussions on digital culture and youth development by offering localized empirical insights into how adolescents negotiate digital influences within everyday social life.